Study Of P450 Enzyme Activity In Liza aurata In The ALKabeer AL Shamaly River Estuary Area - اختيار سمر; سلمان نورا (Latakia University Journal -Biological Sciences Series, 2021)
In this study, we showed that the activity of Cyt-P450 in Liza aurata fish collected from the estuary of the river of Al Kabeer Al Shamaly area, ranges between 2-5 km2. It is considered as one of the methods studying organic pollutants. the biomarkers act as early warning signals on the resulting toxic risks as a reaction to the entry of pollutants into the body. The activity of Cyt-P450 has been studied for male and female of Liza aurata. The result showed that the activity ranged between 2.132 - 29.905 nmol/min/nmol P450 for the males and 2.450, 3.373 and 32.296 nmol / min / nmol p450 for the females. Our research took into consideration some of the environmental factors such as temperature, salinity and conductivity, which showed their direct effects on the activity of Cyt-P450, especially during fertilization periods.